Study on the Chemical Composition and Antioxidant Activities of Amorphophallus sp and Amorphophallus Tuberculatus - Phan, Dao Thi Anh; Pham, Dat Thi Thanh; Le, Tan Hoang (Journal of Technical Education Science, 2025)
Two species of the genus Amorphophallus, Amorphophallus tuberculatus and Amorphophallus sp, have not yet been studied. Therefore, their glucomannan content, chemical compositions, and biological activities were studied in our research. Results showed that the glucomannan content in fresh tubers of Amorphophallus sp ranged from 22.19% to 27.73%, while no glucomannan was detected in A. tuberculatus. The leaf and tube samples were extracted using ethanol-water (70%) as the solvent, and the chemical composition was analyzed using preliminary qualitative methods and FTIR spectroscopy. Antioxidant activities were evaluated through DPPH radical scavenging and ferric reducing antioxidant power (FRAP) assays, which showed that both species exhibited weak antioxidant activities, with IC₅₀ values greater than 100 µg/mL for DPPH and EC₅₀ values above 1.0 mg/mL for FRAP. The chemical composition included flavonoids, saponins, tannins, alkaloids, and polysaccharides, which were identified using preliminary qualitative methods and FTIR spectroscopy. These findings provide fundamental data on the two species’ chemical composition and biological activities, highlighting their potential applications in pharmaceuticals and functional foods, particularly the exploitation of glucomannan as a health-promoting ingredient.